Doses and times of nitrogen application via leaf in the production of corn for silage in the Southern Amazon - Lemes da Rosa, Fellipe; Mitsuo Yamashita, Oscar; Camillo de Carvalho, Marco Antonio; Dallacort, Rivanildo; Maltezo da Rocha, Adriano; de Paula Mera, Lucas (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The objective was to evaluate the application of foliar nitrogen in different doses and times, as a complement to soil fertilization. The work was conducted in a rural area of the municipality of Terra Nova do Norte – MT, located in the southern of brazilian Amazon. The treatments were a combination of foliar applications of nitrogen at doses of 0, 250, 500 and 750 mL.ha-1, and two application times with different intervals: 15 and 40 days after emergence; and 25 and 40 days after the emergency. The experimental design was a randomized block with four replications, in a factorial 4 x 2, totaling eight treatments. It was found that the variables green mass productivity and dried plant and ear and ear length responded positively as the N rates and application times. It was also observed that the foliar application of nitrogen increased the productivity of corn for silage, and better results are obtained from 750 mL.ha-1 of the studied leaf fertilizer. There was no increase in production factors when the foliar application of nitrogen was split.